FEEDING AND REPRODUCTIVE CYCLES OF THE FISH MYSTUS GULIO IN THE COOUM BACKWATERS, MADRAS - Pandian, T J (Indian Journal of Fisheries, 2011)
THIS paper reports on the feeding and reproductive cycles of Mystus gulio in the Cooum backwaters. It is based on the author’s previous work concerning the feeding habits of Megalops cypritioides collected from the same area and during the same period.^ These two species are the most abundant carnivorous fishes in the Cooum backwaters in the vicinity of the University Buildings. A study of their feeding habits may be expected to throw some Ught on the population dynamics of their food organisms too. It may also be interesting to compare the feeding and breeding habits of M. gulio in the Cooum backwaters, with those reported for the same fish in the Hooghly estuary (Pantulu, 1961).